Teaching an Old Dog New Tricks: Past, Present, and Future Priorities For Higher Education Physical Activity Programs. Issue 3 (3rd July 2017) - Stapleton, Drue T.; Taliaferro, Andrea R.; Bulger, Sean M.
ABSTRACT: Physical education programs in colleges/universities have been called on to provide students with opportunities to develop an appreciation for, and increase participation in, lifetime physical activity. Higher Education Physical Activity Programs (HEPAPs) have evolved over the past 100 years in response to changing societal and institutional expectations. The purpose of this article is to celebrate the long history of HEPAPs and recommend innovative strategies for program development that will maintain their position as a valued aspect of campus life. After tracing the historical roots and trends of HEPAPs, the authors suggest (a) adopting a public health perspective, (b) applying theoretical models as a framework for program development, (c) focusing on meaningful learner engagement, and (d) employing learner-centered instructional approaches. Within these overall themes, specific recommendations for program improvement are provided, including the use of alternative content areas, model-based instruction, universal design, instructional technology, and professional development for faculty/staff.